2019
DOI: 10.1002/acn3.50815
|View full text |Cite
|
Sign up to set email alerts
|

Second‐hit DEPDC5 mutation is limited to dysmorphic neurons in cortical dysplasia type IIA

Abstract: Focal cortical dysplasia (FCD) causes drug‐resistant epilepsy and is associated with pathogenic variants in mTOR pathway genes. How germline variants cause these focal lesions is unclear, however a germline + somatic “2‐hit” model is hypothesized. In a boy with drug‐resistant epilepsy, FCD, and a germline DEPDC5 pathogenic variant, we show that a second‐hit DEPDC5 variant is limited to dysmorphic neurons, and the somatic mutation load correlates with both dysmorphic neuron density and the epileptogenic zone. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 23 publications
8
62
0
Order By: Relevance
“…Accordingly, a recent study reported a correlation between interictal EEG spike density and the SLC35A2 variant allele burden from different brain areas of a patient who underwent multilobar resection [ 25 ]. In FCD type 2 and hemimegalencephaly linked to mosaic variants in genes of the mTOR pathway, a similar correlation between the size of the lesion or the epileptogenic activity and the mosaic rate has also been reported confirming the pro-epileptogenic role of mutated cells [ 2 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 68%
“…Accordingly, a recent study reported a correlation between interictal EEG spike density and the SLC35A2 variant allele burden from different brain areas of a patient who underwent multilobar resection [ 25 ]. In FCD type 2 and hemimegalencephaly linked to mosaic variants in genes of the mTOR pathway, a similar correlation between the size of the lesion or the epileptogenic activity and the mosaic rate has also been reported confirming the pro-epileptogenic role of mutated cells [ 2 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 68%
“…Brain tissues were collected at the time of surgery and stored as frozen and formalin‐fixed paraffin‐embedded (FFPE) tissue, taken from the left postcentral gyrus in Patient 1, from the opercular and insular region in Patient 2 (first surgery), and the left medial frontal lobe from Patient 3. Blood and FCD‐derived DNA were sequenced using deep targeted sequencing, and variants were validated by droplet digital PCR (ddPCR), site‐specific amplicon sequencing, or Sanger sequencing as previously described 3,4 . For immunostaining, FFPE tissues were processed and incubated with anti‐Phospho‐S6 Ribosomal Protein (Ser235/236) antibody (Cell‐Signalling, #2211, #4856), a routinely used antibody to assess mTOR activation.…”
Section: Methodsmentioning
confidence: 99%
“…Pathogenic somatic variants restricted to brain tissue in PI3K–AKT–mTOR pathway genes are implicated in a range of cortical malformations 2 . We and others have hypothesized that the lesion size may correlate with the degree of mosaicism (the “variant load”) within dysplastic tissue 3–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Similar indications arise from the demonstration that, in a patient carrying a de novo heterozygous constitutional DEPDC5 mutation (p.Q797Argfs*18), the mutational load of a second somatic hit in the same gene (p.Arg1332*) correlated with dysmorphic neuron density in the dysplastic tissue. 27 Finally, mutations in SLC35A2, at AAF ;6%, cause radiographically nonlesional focal epilepsy, whereas at AAF ;22% cause mild malformations of cortical development. 28,29 The MTOR mutations we identified in patients 1 and 2 (p.Ser2215Phe and p.Leu1460Pro) belong to the subset of recurrent mutations found at low-level somatic mosaicism in FCDII alone 3,[16][17][18]30 (figure 5).…”
Section: Discussionmentioning
confidence: 99%